PENGGUNAAN MEDIA CERITA BERGAMBAR MELALUI APLIKASI ZOOM UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NYARING SISWA KELAS 2 SD CENTRE MALINO - Nurul Fajri Ramadhani; Rohana; Nurfaizah AP (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this study was to determine the improvement of students' reading aloud using illustrated story media through the Zoom application in Indonesian subjects for 2nd grade students of SD Center Malino. This research is a classroom action research which consists of two cycles consisting of cycle I and cycle II. Each cycle has four stages covering, planning, implementing, observing and reflecting. This study lasted for two cycles consisting of cycles. The data collection methods used in this study were as follows: 1) test, 2) observation, and 3) documentation. The focus of this research is to improve the ability to read aloud for grade 2 students of SD Center Malino. The subjects of this study were teachers and students of grade 2 SD Center Malino. The results of this study indicate an increase in students' reading aloud skills from the first cycle in the sufficient category and increased to a good category in the second cycle. The conclusion of this study is that the use of illustrated story media through the zoom application can improve the ability to read aloud for grade 2 SD Center Malino students.